PENGARUH FAKTOR USIA, INDEKS MASSA TUBUH, DAN KADAR GULA DARAH TERHADAP KEJADIAN PENYAKIT DIABETES MELITUS TIPE 2 - Suci, Tri; Ginting, Johannes Bastira (Universitas Prima Indonesia, 2023)
Diabetes Mellitus is a non-communicable and chronic disease; this disease is also generally very closely related to people who are elderly and female. This study aims to determine the effect of age, body mass index, and blood sugar levels on the incidence of type 2 DM. The population of this study was 55,372, which was obtained from secondary data from the offline surveillance form SIPTM (Non-Communicable Disease Information System), Johar Baru Health Center, South Jakarta, 2020; the sample used total sampling. Data analysis using SPSS Ver.25, with bivariate (Chi-Square test) and multivariate (Logistic Regression Enter Method) analysis. The Chi-Square test results showed that the variables of age, body mass index, and blood sugar levels had an association with the incidence of Type 2 DM with a p-value <0.05. The multivariate test results showed that the most influential variable was the blood sugar level variable, with a p-value of 0.00, with OR = 93,302. This means that people with abnormal blood sugar levels have a 93,302 times chance of developing Type 2 Diabetes Mellitus compared to people with normal blood sugar levels. Therefore, the most effective preventive measure for this disease is maintaining blood sugar levels in a normal state to avoid the incidence of Type 2 Diabetes Mellitus, namely by diligently checking blood sugar levels and maintaining a healthy diet and life.